Agenda setting towards residential land use policy in the context of health emergencies the case of barangay Guadalupe, Cebu City, Philippines - Abragan, Clyde Cedrick D.; Aliganga, Junpalo S.; Eata, Earl Max D.; Miralles, Kendrick William S. (College of Social Sciences, University of the Philippines Cebu, 2022)
It is indubitable that land use and urban residential designs significantly affect the exposure of urban residents and other stakeholders to hazards in times of health emergencies, particularly amidst the COVID-19 pandemic. Most importantly, if there is no recent Land Use Plan by the city government or when such is not on its priority agenda. This study delved into the process of agenda-setting concerning the residential land use amidst the pandemic, the case of Barangay Guadalupe, Cebu City in Central Philippines, highlighting the socio-political dynamics of stakeholders, namely: the residents, the local government, businesses, and involved civil society groups. Thematic analysis was utilized, revealing central and critical themes that constitute the level of involvement in the agenda-setting, the problems encountered, and the effects of the residential land use policy to the stakeholders in the context of COVID-19 pandemic. The study found out that there is a large gap between stakeholders in the level of involvement in the agenda setting thereby leading to problems and challenges which are economic, political and socio-cultural. The researchers recommend an enhanced and inclusive multi-sectoral consultations and stakeholder involvement, allowing active participation and collaboration in the agenda setting towards an effective residential land use policy is mandatory under the land space of the pandemic.